Biodiversity of East Asian apple-tree species and their use in breeding - O. N. Barsukova (Труды по прикладной ботанике, генетике и селекции)
Maikop Experiment Station of VIR maintains and studies the richest genetic diversity of primitive East Asian apple-tree species, including the sections Docyniopsis C.C. Schneid. and Sorbomalus Zabel. In addition, the research covers species of the Gymnomeles Koehne section, more advanced in evolutionary development, which, in addition to Siberia and the Far East, are also spread in China, Mongolia and other regions of East Asia. The collection is studied according to VIR’s guidelines.The Docyniopsis section is represented by one of the oldest Malus spp. in the collection – M. sikkimensis (Wenz.) Koehne, inhabiting the Eastern Himalayas. Accession k-2412 is characterized by high yield, disease resistance, and late flowering. The collection contains 5 main species and 6 hybrid ones, belonging to various series of the Sorbomalus section. The Toringonae series (Rehd.) Lang. includes M. sieboldii (Regel) Rehd., spread in Japan, China, and Korea. Of the two accessions of this species, the most promising is k-43201, with a high annual yield, early start of fruiting, and high resistance to diseases. The same series also includes several hybrid species obtained with the participation of M. sieboldii. The most well-known of them is M. × floribunda Sieb. Great prospects for breeding are observed in M. × sargentii Rehd. Accession k-2428 is characterized by a short stem, early start of fruiting, high yield, ornamental traits and, according to long-term data, stable immunity to diseases. The collection harbors a broad diversity of species from the Gymnomeles section. Among them, there are species with a set of valuable traits, including disease resistance, high yield, etc. The most promising is M. hupehensis (Pamp.) Rehd. (k-14945): in addition to disease immunity, it demonstrates high annual yields, exceptional ornamental qualities, and late flowering, in contrast to other species of the Gymnomeles section.